Students’ responses and perception of the indoor environment in the teaching and learning spaces - Mahyuddin, N. (2013)
Poorly operated air conditioning and mechanical ventilation system might cause significant Sick Building Syndrome (SBS) symptoms and thermal discomfort in the hot and humid climate. Thermal comfort in educational building is the important criteria to be considered seriously. The issues related to the occupants’ thermal comfort in work place/educational/residential buildings is given a great attention. However, thermal comfort in the educational building, especially the classroom is really significant to be considered seriously. Indoor environment is important since it affects the health and productivity of building occupants. It can affect the activities of occupants inside the room. The research was performed in the building of Pusat Asasi Sains University of Malaya (PASUM), Malaysia looking into classrooms and laboratories which are mechanically ventilated with air conditioning and ceiling-fans. A combination of both questionnaire surveys and experimental studies were carried out. An adopted questionnaire was distributed to respondents to understand their understandings with regards to the thermal comfort and the indoor environment of their learning spaces. Based on the findings, it was observed that the rooms (classrooms/ tutorial rooms) that incorporated air-conditioned system are more comfortable (temperature average of 25.2˚C) than the rooms (laboratories) which are using the ceiling fan (temperature average of 29.9˚C). The most significant conclusion which can be drawn from this research is that none of the learning spaces had thermal conditions falling within the comfort zone of ASHRAE standard 55. Students found temperature range beyond the comfort zone acceptable.